West Bank and Gaza : Report to the Ad Hoc Liaison Committee. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
This IMF report to the AHLC is the first since September 2018. Following limited engagement over the past three years, policy discussions have intensified in recent months. These discussions have focused mainly on establishing a medium term macro-fiscal framework, including the broad outlines of a reform scenario.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; West Bank and Gaza